ANALYSIS OF THE CONCEPT OF INNOVATIVE PEDAGOGY: PROBLEMS AND SOLUTIONS - Ortiqova Nargiza Akramovna (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2023)
This article analyzes the concept of innovative pedagogy. Also stated is the need to transform educational reforms with international trends.